ESTABLISHING NEW TRADE AND ECONOMIC PATTERNS IN DEMOCRATIC ERA: THE IMPLICATIONS FOR MONGOLIA - Alicia Campi (Acta Mongolica, 2011)
When Mongolia entered its democratic transition in 1990, after 70 years of isolation from the economic development of most of its Asian neighbors, Mongolian policymakers expected that their nation, after making the necessary free market reforms, would be able to benefit from successful integration into the booming regional market and the rest of the developed world. More than twenty years later, Mongolia has extensively reorganized its economy along free market lines, joined the WTO in 1997, and opened its own economy to extensive foreign direct investment (FDI). While to be sure this has resulted in very concrete and substantial gains for the nation in GDP growth and in increased prosperity for some segments of the population, it has brought even more challenges for government leaders to wrestle with, including rising income disparities and poverty in society, unemployment, growing corruption, and environmental damage. However, what may prove to be the most significant negative result, which was clearly anticipated but not avoided, has been the growing potential danger to the nation’s sovereignty and national identity by the monopolization of its economy by its Chinese southern neighbor. China’s potential and historical desire to monopolize Mongolia’s economy was well understood by Mongolian policymakers, and not just an exaggeration foisted upon them by the Soviets. I believe that this point of view was not seriously taken into consideration by the Western donors and multilateral organizations that were working with the Mongols to establish the mechanisms of a new free market economy, and ultimately they promoted policies and regulations which overwhelmed Mongolian concerns about the role of China and are greatly responsible for the present-day Chinese monopolization of Mongolian trade and FDI.